Covalent and non-covalent chemistry of 2D black phosphorus - Mitrović, Aleksandra (RSC Adv, 2021)
The post-graphene era is undoubtedly marked by two-dimensional (2D) sheet polymers, such as black phosphorus (BP). This emerging material has a fascinating structure and outstanding electronic properties and has been postulated for a plethora of applications. The need to circumvent the pronounced oxophilicity of P atoms has dominated the research on this material in recent years, with the objective of finding the most effective method to improve its environmental stability. When it comes to chemical functionalization, the few approaches reported so far involve some drawbacks such as low degree of addition and low production ability. This review presents the concepts and strategies of our studies on the chemical functionalization of BP, both non-covalent and covalent, emphazising the current synthetic challenges. Moreover, we also provide some effective pathways for the chemical activation of the unreactive basal plane, the identification of the effective binding strategies, and the concept to overcome hurdles associated with characterization tools. This work will provide fundamental insights into the controlled chemical functionalization and characterization of BP, fostering the research on this appealing 2D material.